Physical education students’ understanding level about the rice method for sports injuries - Masfufah, Sri; Handayani, Heni Yuli; Purwoto, Septyaningrum Putri; Himawan, Agus; Utami, Tri Setyo (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
The research was carried out to investigate how high the level of students’ understanding of the RICE method was, where before this research, students had already studied the First Aid course. Therefore, following up on how well students understand the RICE method is crucial. Moreover, research has emerged regarding students’ understanding of the RICE method for sports injuries. Thus, this research aimed to explore how much students understand the RICE method in dealing with injuries during sports. This research applied descriptive, and a survey was used as the data collection technique. Data obtained from research results on 27 students’ understanding of the RICE method in treating injuries was measured based on a questionnaire that had been distributed with 30 questions with a score range of 0-1. The results show that the class of 2020 Physical Education students need a predominantly better understanding of the RICE Method for treating sports injuries. Specifically, 0% of students fell into the very good, good, or sufficient categories, while 93% were classified as poor and 7% as very poor. This indicates that all students’ comprehension level of the RICE method needs more improvement.